Effect of temperature on the crystalline phase and dielectric and ferroelectric properties of poly(vinylidene fluoride) film. (May 2014) - Yang, Lu; Ji, Hongli; Qiu, Jinhao; Zhu, Kongjun; Shao, Bin
As a functional polymer material, poly(vinylidene fluoride) has attracted broad attention due to its outstanding electroactive properties. The electroactive properties of poly(vinylidene fluoride) depend greatly on its crystalline structure, which in turn depends on the processing conditions. In our recent study, poly(vinylidene fluoride) films were prepared by a solution crystallization method, and the effect of evaporation temperatures on the crystalline phase, crystallinity, and morphology of poly(vinylidene fluoride) was investigated. The results reveal that evaporation temperature is the key factor when studying crystalline structure of poly(vinylidene fluoride). Low temperatures can facilitate the nucleation of β-phase; however, they are disadvantageous for the crystal nucleation and crystal growth. It was also found that the dielectric and ferroelectric properties are closely related to the crystallinity of β-phase of poly(vinylidene fluoride) films. Moreover, the porous structure formed in low evaporation temperatures can lead to a decline in dielectric property and breakdown strength. The films fabricated at 80 °C owned the highest crystallinity of β-phase (49%) and presented the maximum ε r (12.5, 10 3 Hz) and P r (7 µC/cm 2 ), suggesting that the optimum temperature to prepare poly(vinylidene fluoride) films with excellent electroactive properties is 80 °C.